High ranges : problems and potential of a hill region in the Southern Western ghats - Nair, Sathis Chbandran (New Delhi, 1994)
The greatest asset of our country is the incomparable potential of its people. Yet the most serious threat the country faces is not its lack of development or its large population but the unprecedented and rapidly accelerating degradation that our land and natural resource base is being subjected to, and the gross under-utilization and misuse of the human potential. These two are interrelated because the natural environment plays a crucial role in moulding the culture and identity of the people. Degradation of environ ment affects the physical and cultural fibre of the people. The degradation of people has its negative impact on the environ ment. These simple interrelations and feedback linkages are well known and need not be restated. Rather, one may attempt to spell out in specific terms how far a particular area is degraded and then project a scenario of how the human communities will be affected. A good understanding of the ecological processes at work in that area may even enable us to specify how far-reaching in space and time the influences of a man-modified environment could permeate. For in stance, the modulating influences of the hill ranges and permeating influences through drainage basins are fairly well known and can be chartered.
Keywords: Environment